Corporate Vulnerabilities in the Middle East, North Africa, and Pakistan in the Wake of COVID-19 Pandemic - Abidi, Nordine (IMF Working Papers; Working Paper ;, 2022)
This paper analyzes corporate vulnerabilities in the Middle East, North Africa and Pakistan (MENAP hereafter) in the wake of the COVID-19 pandemic shock. Using a sample of nearly 700 firms from eleven countries in MENAP, we assess the non-financial corporate (NFC) sector's liquidity and solvency risk and viability over the medium term under different stress test scenarios. Our findings suggest that the health crisis has exacerbated vulnerabilities in the corporate sector, though the effects are heterogenous across the region. Small firms, which entered the pandemic in a more vulnerable position, would remain under high liquidity stress over the medium term, putting a substantial share of these firmsa' debt at risk of default. Similarly, liquidity needs of firms in contact-intensive sectors have also worsened and would remain elevated in 2022-23. We also show that an adverse scenario of subdued growth and premature withdrawal of policy support would impair the capacity to service interest expenses, especially among small firms, resulting in higher insolvency risk. Overall, our results indicate that some segments of the MENAP corporate sector could remain reliant on policy support during the recovery phase and that structural reforms are critical to save distressed but viable firms from bankruptcy and ensure an efficient liquidation of "zombie" firms.